2012
DOI: 10.1590/s2179-64912012000400016
|View full text |Cite
|
Sign up to set email alerts
|

Acompanhamento do aleitamento materno no tratamento de crianças com fenilcetonúria

Abstract: A fenilcetonúria (PKU) ocorre na incapacidade para transformar fenilalanina em tirosina, trazendo efeitos tóxicos para o sistema nervoso central. Tradicionalmente, no tratamento da PKU, o aleitamento materno é substituído por fórmula láctea. Este estudo verificou os efeitos do aleitamento materno como fonte de fenilalanina no desenvolvimento de crianças com PKU. Participaram dez lactentes com PKU, que iniciaram o tratamento com a introdução de fórmula láctea antes dos 30 dias e que mantiveram o aleitamento mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 12 publications
0
13
0
1
Order By: Relevance
“…(F) Growth curves of strain A118 in LB supplemented with 0.02% PA, 0.02% PAA, or 0.02% PP with or without PF. 0.02% was selected as the concentration for PA and its derivatives for testing in order to mimic the mean concentration of amino acid nitrogen in normal human blood (Schaeffer et al, 1975; Lamonica et al, 2012). Statistical analysis was performed using Mann–Whitney ( n = 3).…”
Section: Resultsmentioning
confidence: 99%
“…(F) Growth curves of strain A118 in LB supplemented with 0.02% PA, 0.02% PAA, or 0.02% PP with or without PF. 0.02% was selected as the concentration for PA and its derivatives for testing in order to mimic the mean concentration of amino acid nitrogen in normal human blood (Schaeffer et al, 1975; Lamonica et al, 2012). Statistical analysis was performed using Mann–Whitney ( n = 3).…”
Section: Resultsmentioning
confidence: 99%
“…Morão et al [70] found that the patients also showed a loss in the score of the Children Gambling Task. Lamônica et al [59] reported that out of 10 patients, two of them presented outside the normality standards in the development scales. The skills were related to performance in motor, linguistic and cognitive activities.…”
Section: Descriptive Analysis Of Single Studies Reporting the Outcome...mentioning
confidence: 99%
“…In the case series studies (Fig. 2, panel B), three domains (ie, clear description of both patient's history and postintervention clinical condition, and description of a takeaway lesson) were rated as "high risk of bias" in three studies (25.0%) [21,59,97].…”
Section: Risk Of Bias Assesmentmentioning
confidence: 99%
See 2 more Smart Citations